BORON ISOTOPIC GEOCHEMISTRY OF CARBONATES AND PORE WATERS, OCEAN DRILLING PROGRAM SITE 851 - Spivack A.J.; You C.F. (My University, 1997)
We have determined the boron content and isotopic composition of bulk carbonates and associated pore waters from Ocean Drilling Program Site 851. The δ11B of the carbonates range from 23%% to as low as -5.5%%, greatly extending the range of reported carbonate δ11B values. In contrast, pore fluid isotopic compositions are relatively constant. Based on the correlation of δ11B and 1/B (r=0.99) we conclude that the bulk carbonate at this site is a mixture of a biogenic component (~7 ppm with δ11B of 23%%) and a recrystallized component (~2.5 ppm with δ11B of -5.5%%). The empirical `low pH' water-carbonate fractionation factor implied by the data is 0.959+/-0.003. A boron concentration minimum occurs in pore waters at a depth of approximately 200 m below the seafloor and this is interpreted as reflecting essentially quantitative uptake of B at this depth and the horizontal advection of pore fluids with water residence times below the minimum on the order of 3,600 years.
Keywords: BORON; CARBONATES; PORE WATER; ODP SITE 851; GEOCHEMISTRY